Flexible and Hierarchical Metal–Organic Framework Composites for High‐Performance Catalysis. Issue 29 (14th June 2018) - Huang, Ning; Drake, Hannah; Li, Jialuo; Pang, Jiandong; Wang, Ying; Yuan, Shuai; Wang, Qi; Cai, Peiyu; Qin, Junsheng; Zhou, Hong‐Cai
Abstract: The development of porous composite materials is of great significance for their potentially improved performance over those of individual components and extensive applications in separation, energy storage, and heterogeneous catalysis. Now mesoporous metal–organic frameworks (MOFs) with macroporous melamine foam (MF) have been integrated using a one‐pot process, generating a series of MOF/MF composite materials with preserved crystallinity, hierarchical porosity, and increased stability over that of melamine foam. The MOF nanocrystals were threaded by the melamine foam networks, resembling a ball‐and‐stick model overall. The resulting MOF/MF composite materials were employed as an effective heterogeneous catalyst for the epoxidation of cholesteryl esters. Combining the advantages of interpenetrative mesoporous and macroporous structures, the MOF/melamine foam composite has higher dispersibility and more accessibility of catalytic sites, exhibiting excellent catalytic performance. Abstract : Ball‐and‐stick catalysis : A series of flexible and hierarchical MOF composites have been developed by integrating mesoporous MOFs with macroporous melamine foam (MF) using a one‐pot process. These composite materials can be employed as an effective heterogeneous catalyst for epoxidation reactions.